2017
DOI: 10.32677/ijcr.2017.v03.i03.005
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Seizures During Cataract Surgery Following Peribulbar Block: A Case Report

Abstract: Local anesthesia techniques are commonly used to perform the cataract surgery. Among these techniques, peribulbar anesthesia (PBA), when compared to retrobulbar anesthesia, is more effective and safe. However, PBA is not without risk. Complications may arise which if not recognized early and resuscitated, can be fatal. A 70-year-old Indian female was admitted for cataract extraction and lens implant in her left eye. Lignocaine sensitivity was done and showed no abnormal reaction. She developed generalized toni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 20 publications
(21 reference statements)
1
4
0
Order By: Relevance
“…In this respect, our case was similar to that of Bensghir et al [8]. Paul et al [9] reported a case of BSA after the peribulbar block where the presentation was convulsion similar to ours, without respiratory arrest followed by prolonged hypotension requiring vasopressor agents.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In this respect, our case was similar to that of Bensghir et al [8]. Paul et al [9] reported a case of BSA after the peribulbar block where the presentation was convulsion similar to ours, without respiratory arrest followed by prolonged hypotension requiring vasopressor agents.…”
Section: Discussionsupporting
confidence: 89%
“…BSA is a rare but serious complication of the peribulbar block. To the best of our knowledge, fewer than ten cases have been reported in the literature [4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several mechanisms may lead to CNS spread of local anesthetics during peribulbar anesthesia. Clinical signs typically have a rapid onset and can range from loss of consciousness to cardiac arrest [22]. Firstly, an inadvertent intra-arterial injection in the ophthalmic artery or into one of its branches can occur.…”
Section: Nd Not Describedmentioning
confidence: 99%
“…Convulsions following peribulbar block could be attributed to the oculocardiac reflex, hypoglycemia, hypoxia, or pro-stroke toxicity of local anesthetics [7,22,26]. Although the mechanisms of seizures are not known, it is speculated that there is a selective blockage of inhibitory synapses.…”
Section: Nd Not Describedmentioning
confidence: 99%